Confidence to return to play after ACL reconstruction: An evaluation of quadriceps strength symmetry and injury mechanism in male athletes - Straub, R. K.; Della Villa, F.; Mandelbaum, B.; Powers, C. M. (Sports Health: A Multidisciplinary Approach, 2021)
Background: After anterior cruciate ligament reconstruction (ACLR), diminished quadriceps strength symmetry and reduced psychological readiness to return to play (RTP) increase the risk for subsequent injury. Although the relationship between quadriceps strength symmetry and psychological readiness to RTP has been reported to be influenced by injury mechanism in female athletes, it is unclear whether such a relationship exists in male athletes.